Development of impurity seeding and radiation enhancement in the helical divertor of LHD. (14th July 2015) - Mukai, K.; Masuzaki, S.; Peterson, B.J.; Akiyama, T.; Kobayashi, M.; Suzuki, C.; Tanaka, H.; Pandya, S.N.; Sano, R.; Motojima, G.; Ohno, N.; Morisaki, T.; et al.
Abstract: Impurity seeding to reduce the divertor heat load was conducted in the large helical device (LHD) using neon (Ne) and krypton (Kr) puffing. Radiation enhancement and reduction of the divertor heat load were observed. In the LHD, the ratio between the total radiated power and the heating power, f rad = P rad / P heating, is limited up to around 30% in hydrogen plasmas even for high density plasma just below the radiative collapse ( n e, bar > 1 × 10 20 m −3 ), where n e, bar is the line averaged density. With Ne seeding, the ratio could be raised to 52% at n e, bar 1.3 × 10 19 m −3, albeit with a slight reduction in confinement. f rad 30% could be sustained for 3.4 s using multi-pulse Ne seeding at n e, bar 4 × 10 19 m −3 . The localized supplemental radiation was observed along the helical divertor X-points (HDXs) which is similar to the estimated structure by the EMC3-EIRENE code. Kr seeding was also conducted at n e, bar 3.1 × 10 19 m −3 . f rad 25% was obtained without a significant change in stored energy. The radiation enhancement had a slower time constant. The supplemental radiation area of the Kr seeded plasma moved from the HDXs to the core plasma. Highly charged states of Kr ions are considered to be the dominant radiators from the plasma core region.